Development of PE teaching materials on variations of fundamental locomotor movements toward elementary school - Afiq Hakim Mujtahidin; Heryanto Nur Muhammad; Afifan Yulfadinata; Afiq Hakim Mujtahidin; Heryanto Nur Muhammad; Afifan Yulfadinata (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2026)
The aim of this research is to determine the effect of developing basic locomotor movement teaching materials on student learning outcomes in elementary schools. This research uses the Research and Development (R&D) method with the ADDIE instructional design model (Analysis, Design, Development, Implementation, and Evaluation), which aims to develop and test the effectiveness of learning products in the form of basic locomotor movement teaching modules. The research subjects were phase B students, namely fourth grade elementary school students of SD Negeri Kebraon 1 Surabaya. The data collection instrument used is a learning outcomes test to measure students’ abilities before and after implementing the developed teaching module. The data analysis technique was carried out using the paired sample t-test to determine differences in student learning outcomes before and after being given treatment. Based on the results of data analysis, it can be concluded that the development of the basic locomotor movement teaching module has had a significant influence on improving student learning outcomes, so that the developed teaching module is declared effective and suitable for use in PE learning in elementary schools.